Carcass characteristics of feedlot-finished Nellore heifers slaughtered at different weights - Rezende, Pedro Leonardo de Paula; Restle, João; Bilego, Ubirajara Oliveira; Fernandes, Juliano José de Resende; Missio, Regis Luis; Guimarães, Tiago Pereira (Acta Scientiarum. Animal Sciences, 2019)
Carcass and meat characteristics of 48 Nellore heifers at 24 to 30 months of age, with an initial weight of 263.4 ± 13.9 kg, were evaluated. The experiment was set up as a completely randomized design with four treatments, which consisted of four slaughter-weight classes, namely <340, 340-370, 370-400, or >400 kg. Back fat thickness was not influenced (p > 0.05) by slaughter weight in any of the forms it was expressed (mm or %), averaging 5.3 mm. Loin eye area in cm2 increased (p < 0.05) with the increase in slaughter weight. Animals slaughtered at a live weight (LW) of more than 400 kg showed better (p < 0.05) carcass conformation than the other experimental groups (9.8 points). Heifers slaughtered at over 400 kg LW had a more compact (p < 0.05) carcass (1.65 cm kg-1 cold carcass). The marbling degree of meat was lower (p < 0.05) in the animals slaughtered at less than 340 kg LW. In conclusion, cull heifers must not be slaughtered at a LW of less than 340 kg and slaughter weights greater than 400 kg have positive implications on important carcass characteristics, notably conformation and marbling.